Alphaworld: when i was sick - Talia, James (Oxford University Press Melbourne, 2004)
When I was sick, everything felt different. The world outside seemed distant, and simple activities became challenging. I spent a lot of time resting, wrapped in blankets, trying to find comfort. The days blurred together, filled with moments of fatigue and the occasional flicker of hope as I started to feel better. Friends and family checked in, sending messages of support that brightened my spirits. Despite the discomfort, it was a time of reflection and gratitude for the little things, like a warm cup of tea or a favorite book. Eventually, as I regained my strength, I looked forward to rejoining the world with a newfound appreciation for health and vitality.